Procesos de subjetivación política en el acuerdo nacional de jóvenes (2007-2014) de mayo del 2015 a mayo del 2016 - Cevallos Chávez, José Luis (2016)
The present paper makes an approach to the processes of political subjectivisation in the young people who participated in The National Agreement of the Young. The same agreement that was previously held in the Constitutional Assembly of 2008. Through Social and Political Psychology we make a theoretical journey analyzing the interviews done to the organizational leaders of the young who participated in the National Agreement. Here we can recognize the dimensions which influence the political subjectivisation like historic awareness, reflexivity and the action articulation. The study of the dimensions previously mentioned is linked in a direct way to the political socialization processes which were achieved through the work of the young. This work was prior to the National Assembly of 2008. All of this allowed us to analyze the young people’s conception of youth and politics. This conception was developed through political subjectivisation, allowing them to be an active part of the 2008 Assembly.